2016
DOI: 10.1080/02602938.2016.1260091
|View full text |Cite
|
Sign up to set email alerts
|

A cyclical self-assessment process: towards a model of how students engage in self-assessment

Abstract: While significant progress has been made on understanding the effects of student selfassessment, the processes by which these effects occur is much less studied empirically. The present research identified the actions involved in a cyclical self-assessment process. In this qualitative study, seventeen undergraduate students from a teacher education institute took part in in-depth interviews focusing on the common actions students normally undertake to self-assess. The findings identified the following three ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 48 publications
6
117
1
9
Order By: Relevance
“…Self-assessment is a fundamental skill required at each phase of self-regulated learning (Yan, 2019) and is crucial for life-long learning (Boud, 1995;Tan, 2012). Through self-assessing their own performances, students can identify their strengths and weaknesses, and adjust their learning strategies accordingly to learn more (Boud, 1995;Yan and Brown, 2017). Recent review studies (e.g., Brown and Harris, 2013;Panadero et al, 2017) revealed a general consensus in the literature with regard to the positive impact of self-assessment on academic achievement, self-regulation, and motivational aspects of learning (e.g., self-efficacy), although the effect sizes varied across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assessment is a fundamental skill required at each phase of self-regulated learning (Yan, 2019) and is crucial for life-long learning (Boud, 1995;Tan, 2012). Through self-assessing their own performances, students can identify their strengths and weaknesses, and adjust their learning strategies accordingly to learn more (Boud, 1995;Yan and Brown, 2017). Recent review studies (e.g., Brown and Harris, 2013;Panadero et al, 2017) revealed a general consensus in the literature with regard to the positive impact of self-assessment on academic achievement, self-regulation, and motivational aspects of learning (e.g., self-efficacy), although the effect sizes varied across studies.…”
Section: Introductionmentioning
confidence: 99%
“…(student blog1, post 2), or "we had great discussions together over how self-assessment works and how it helps our understanding and learning"(student blog 9, post 2); and (2) students who were involved in self-assessment as a means of ticking off a check list, focused on the related rubric criteria and the feedback of the lecturer to get a high grade too: "self-assessing the group project was like 'ticking off a checklist' and seeing if we had included all the necessary characteristics" (surface learning approach)(student blog 34, post 2).The study of Yan & Brown (2016), also demonstrated that both feedback and reflection are indispensable elements to self-assessment. As highlighted by Dinsmore and Wilson (2016), students who were not engaged in meaningful reflective thinking were less likely to make strategic adjustments to their learning strategies since they were unaware of their strengths and weaknesses: "When I see the self-assessing sheet I do not strive for passing, I look to see what the A level grade is.…”
Section: Resultsmentioning
confidence: 99%
“…For this study the self-directed feedback seeking of the Yan and Brown (2016) proposal, was oriented by an in-class general feedback, to support the pre-service teachers in their first self-assessment experience. Overall, results conveyed two main insights: (1) students who were involved in self-assessment as a process of self-reflection that provoked a deep content learning approach, high engagement and high final grades: "by doing this when we went to self-assess ourselves it gave ourselves another opportunity to critically analyze our project and ensure we had all aspects of the criteria included"…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations